Campus sustainability initiatives and performance: do they correlate?. Issue 4 (6th July 2015) - Lang, Tim
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to test the hypothesis that there are correlations between campus sustainability initiatives and environmental performance, as measured by resource consumption and waste generation performance metrics. Institutions of higher education would like to imply that their campus sustainability initiatives are good proxies for their environmental performance. Design/methodology/approach – Using data reported through the Association for the Advancement in Higher Education's Sustainability Tracking and Rating System (AASHE STARS) framework, a series of univariate multiple linear regression models were constructed to test for correlations between energy, greenhouse gas (GHG), water and waste performance metrics, and credit points awarded to institutions for various campus sustainability initiatives. Findings – There are very limited correlations between institutional environmental performance and adoption of campus sustainability initiatives, be they targeted operational or coordination and planning best practices, or curricular, co-curricular or research activities. Conversely, there are strong correlations between environmental performance and campus characteristics, namely, institution type and climate zone. Practical implications – Institutional decision makers should not assume that implementing best practices given credit by AASHE STARS will lead to improved environmental performance. Those assessing institutional sustainability should be wary of institutions who cite initiatives to imply a certain level of environmental performance or performance improvement. Originality/value – This is the first paper to use data reported through the AASHE STARS framework to assess correlations between campus initiatives and environmental performance. It extends beyond previous research by considering energy, water and waste performance metrics in addition to GHG emissions, and it considers campus sustainability initiatives in addition to campus characteristics.